Znaczenie prawno-ekonomicznych instrumentów polityki ekologicznej w stymulowaniu postępu technicznego - Zajączkowski, Krzysztof (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
The purpose of this report is to show how effective the currently used legal and economic instruments of the environmental policy stimulate the technical progress in the field of environmental protection and simultaneously how contribute to the conservation of natural resources. Recently observed changes in the climate and their projected future impacts cause that governments and international organizations of the public law adopt successive international and legally binding agreements, e.g. the Kyoto Protocol linked to the United Nations Framework Convention on Climate Change, which necessitate the implementation of the restrictive provisions, thanks that help stimulate green investment and help countries meet their emission targets in a cost-effective way. Nowadays, the significant role in achieving the objectives is assigned to the implementation of new technologies, which on the one hand contribute to the effective protection of the environment, on the other - to increase the competitiveness of regions using advanced technologies.
Keywords: ochrona środowiska; prawne i ekonomiczne instrumenty; protokół z Kioto; konwencja o zmianach klimatu; postęp techniczny